Μελέτη συμπεριφοράς του μυκητοκτόνου Azoxystrobin σε κυπριακά εδάφη - Ζάκου, Παναγιώτα (Τμήμα Επιστήμης και Τεχνολογίας Περιβάλλοντος, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2018)
Agriculture, for over 50 years, is highly based on the use of pesticides for the protection of crops from parasites and diseases. Even though people are heavily dependent on the ground for survival and food, they continuously destroy it by the inappropriate use of pesticides. As Greenpeace says, "Europe's toxic addiction", instead of being used as a final solution to face serious and rare diseases or illnesses, has become fashion and farmers dependence on them is obvious. They pose a risk both to the human health and the environment. The result of a pesticide on the soil depends on many factors and these will determine its impact on the environment. The purpose of this dissertation was to examine the behavior of three different commercial formulations of the fungicide Azoxystrobin in three soil samples from different areas. The formulations were contained Azoxystrobin 20% w/v, 25% w/v and 100% w/v. Firstly, the fungicides were introduced into the three soil samples and then extracted with acetone and CaCl2. The process of collecting the samples from each area, took place at 5 time points which consisted of day 0, 7, 14, 21 and 100. The gas chromatograph was used to detect the substance. The results were recorded in tables analyzed appropriately, so that the relevant conclusions could be drawn for their behavior in the soils. The extraction rates of Azox in the two formulations are significantly affected by the other substances they contain, such as the active substance Difenoconazole and are quite different from the extraction rates for the fungicide with 100% Azox. The results showed satisfactory extraction rates of Azox for the two formulations, with the exception of the soil from the Vrysoules area, which for the 20% formulation, the rate of extraction decreases. For the 100% Azox fungicide, the extraction rates are reduced for all three soils, relative to the initial concentration applied. From this we conclude that part of the fungicide is adsorbed or disintegrated. The behavior of each plant protection substance in soils depends on various physicochemical and biological processes and from the composition of each soil. The residence time of the plant protection product in soils is determined by its species and its physicochemical properties. The Azox extraction method using organic acetone solvent is a trustworthy one.
Keywords: Azoxystrobin; Parasites; Diseases; Φυτοπροστατευτικές ουσίες; Συμπεριφορά στο έδαφος